Pengaruh Struktur Modal, Pertumbuhan, Ukuran Perusahaan dan Likuiditas terhadap Profitabilitas pada Perusahaan Pertambangan Periode 2012-2016 - Uyung Sutan Indomo (Jurnal Ekonomi, 2019)
This study aims to analyze the effect of capital structure, growth, company size and liquidity simultaneously on the profitability of mining companies listed on the Indonesia Stock Exchange for the period 2012-2016. This study uses a causal research method through hypothesis testing. The population of this study were 40 mining companies listed on the Indonesia Stock Exchange for the period 2012-2016. Sample selection was carried out using non-probability sampling method with purposive sampling technique in order to obtain as many as 36 companies. The type of data used in this study is secondary data, in the form of financial report data sourced from the Indonesian Capital Market Directory (ICMD) and the Indonesia Stock Exchange. The data obtained from the results of the next study were analyzed by using panel data regression models using the Eviews 9.0 software program.The summary of the results of this study is first, capital structure has been shown to have a significant negative effect on profitability. Second, company growth has a significant positive effect on profitability. Third, firm size has a positive and insignificant effect on profitability. Fourth, liquidity has a significant negative effect on profitability. Based on the results of research conducted, it is evident that capital structure, company growth and liquidity have a significant influence on company profitability. So it is suggested to investors to ensure that the company's managerial management manages the capital structure as efficiently and effectively as possible and considers how the managerial utilizes and manages all the resources owned by the company to increase its business growth and should pay more attention to the company's liquidity because it has been proven to affect the company's profitability.